Manuskrip La Galigo dalam Tradisi Massure’ di Wajo-Sulawesi Selatan - Hamsiati Hamsiati; Wardiah Hamid; Mustolehudin (Jurnal Lektur Keagamaan, 2021)
The La Galigo Manuscript is the longest literary work in the world, which is the ancestral heritage of the people of South Sulawesi. These manuscripts contain knowledge, traditions, religion, and art. This paper aims to explore the La Galigo manuscript in the massure' tradition in Wajo. Methods of collecting data through interviews, observation, and documentation. The findings show that the existence of the La Galigo manuscript in Wajo is partly a private collection of the community. This manuscript, in the context of socio-religious culture, is practiced through the massure art tradition by the Bugis Wajo community. The Massure' tradition can be found in Bugis community ceremonies such as the maddoja bine tradition, mappenre' tojang, menre' bola baru (rising to a new house), tudang penni (pre-wedding night party), and cultural festivals in Wajo. Keywords: La Galigo, Manuscript, Massure', Wajo   Manuskrip La Galigo merupakan karya sastra terpanjang di dunia, yang merupakan warisan nenek moyang masyarakat Sulawesi Selatan. Manus-krip ini memuat tentang pengetahuan, tradisi, agama dan kesenian. Tulisan ini bertujuan mengeksplorasi manuskrip La Galigo dalam tradisi massure’ di Wajo. Metode pengumpulan data melalui wawancara, observasi dan dokumentasi. Hasil temuan menunjukkan keberadaan manuskrip La Galigo di Wajo sebagian merupakan koleksi pribadi masyarakat. Manuskrip ini dalam konteks sosial budaya keagamaan, dipraktikkan melalui tradisi kesenian massure’ oleh masyarakat Bugis Wajo. Tradisi Massure’ dapat dijumpai pada upacara-upacara masyarakat Bugis seperti dalam tradisi maddoja bine, mappenre’ tojang, menre’ bola baru (naik rumah baru), tudang penni (pesta malam pra akad nikah), dan festival kebudayaan di Wajo. Kata Kunci: La Galigo, Manuskrip, Massure’, Wajo